Trees of the Central Valley of Costa Rica: reproduction. Carboncillo (Acacia angustissima (Mill.) Kuntze) - Rojas-Rodríguez, Freddy (2013)
The following issue presents a brief description about the “carboncillo” tree (Acacia angustissima (Mill.) Kuntze) including information about its phenology which directly relates to fruit recollection, seed treatment, nursery, and germination processes.